(untitled) (International Journal of Engineering and Computer Science, 2014)
The purpose of this study was to achieve new directions towards engineering education. Our survey states that although Traditional Methods (TM) are considered to be good teaching methods but students rated Team Based Methods (TBM) as the most interesting ones. The result of this study indicates that the students are more inclined towards newer methods of teaching like Computer Aided Method (CAM) or Team Based Methods (TBM). For instance, 70% of students from Chemical Engineering and Environmental Science and Technology voted ‘excellent’ for Industrial visit. We can say that they wanted to learn more by practice or by going through the real.